Experimental investigation of concrete incorporating HDPE plastic waste and metakaolin. (2021) - Punitha, V.; Sakthieswaran, N.; Ganesh Babu, O.
Abstract: This paper deals with the investigation of using Metakaolin and HDPE plastic waste with various percentages in concrete to make the concrete economical with desired properties and to reduce the consumption of naturally available construction materials. Six percentages of High Density Polyethylene (HDPE) Plastic powder (5%, 10%, 15%, 20%, 25% and 30%) and 10% metakaolin are incorporated with the weight of fine aggregate and cement respectively. The concrete with 10% metakaolin and 15% HDPE plastic powder gives better result on compressive strength in comparison with conventional concrete. The flexural strength and split tensile strength of concrete shows up to 80% and 90% replacement with 10% metakaolin and 5% HDPE plastic powder respectively.